Researches on the effect of biofeedback training on cognitive processes and emotional states (The Journal of Psychology and Sociology, 2021)
Biofeedback method is a perspective approach in the behavioral psychiatry. It is widely used in clinical practice for correction of psychophysiological disorders, as well as for enhancement of cogni- tive abilities, productivity, stress tolerance, depression, etc. As this method is non-invasive and does not require medication, there is a relatively low risk of undesirable side effects in comparison with other means of treatment.In this paper the familiarization and applications of biofeedback are presented. A special accent is made in regard to literature review on the theme of enhancement of attention in health and correction of depressive state. According to the conducted studies, it was revealed that the main methods ap- proaches for attention improvement in health with the use of neurofeedback are trainings for increasing beta rhythms (12-18 Hz) and theta rhythms suppression (4-7 Hz), as well as SMR training (12-15 Hz). This article also provides a review of the literature on biofeedback devoted to the problem of the depres- sive state. Researches show that biofeedback trainings aimed in increasing alpha rhythms (8-12 Hz) and altering alpha asymmetries in the prefrontal regions of the brain show positive effect on the depression reduction.Key words: biofeedback, attention, depression.